2014
DOI: 10.3233/jad-140066
|View full text |Cite
|
Sign up to set email alerts
|

Tubastatin A/ACY-1215 Improves Cognition in Alzheimer's Disease Transgenic Mice1

Abstract: Histone deacetylase 6 (HDAC6) is currently being discussed as a promising therapeutic target for the treatment of Alzheimer's disease (AD). Mounting evidence indicates that increased HDAC6 expression may contribute to AD-associated neurodegeneration, although beneficial effects have also been identified. In the present study, we tested the potential of two selective HDAC6 inhibitors, tubastatin A and ACY-1215, to rescue cognitive deficits in a mouse model of AD. We found that both tubastatin A and ACY-1215 all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 52 publications
8
114
2
1
Order By: Relevance
“…In agreement with our findings, HDAC6 inhibition was recently reported to induce autophagic flux in primary cardiomyocytes [52] and to facilitate the autophagic degradation of A and hyperphosphorylated tau [53].…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…In agreement with our findings, HDAC6 inhibition was recently reported to induce autophagic flux in primary cardiomyocytes [52] and to facilitate the autophagic degradation of A and hyperphosphorylated tau [53].…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…In fact, the induction of genes implicated in synaptic plasticity, the formation of new dendritic spines, and the increase in pCamKII observed in mice treated with CM-414 may at least partially underlie the restoration of memory in these transgenic mice. Finally, the inhibition of HDAC6 may facilitate the degradation of misfolded proteins, such as Aβ and pTau (Sung et al, 2012;Yu et al, 2013;Zhang et al, 2014). Although different studies have demonstrated that HDACi or PDE5i improved cognitive deficits in animal models of AD, their role on amyloid pathology is controversial (Benito et al, 2015;Cuadrado-Tejedor et al, 2011b;Garcia-Barroso et al, 2013;Puzzo et al, 2009;Qing et al, 2008;Ricobaraza et al, 2009;Rumbaugh et al, 2015;Zhang and Schluesener, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these enzymes have been described as negative regulators of memory consolidation (Guan et al, 2009;McQuown et al, 2011). In contrast, HDAC6 regulates microtubule function and stability via tubulin acetylation (Guan et al, 2009;Hubbert et al, 2002), and dampening HDAC6 activity promotes tau and Aβ clearance (Cook et al, 2012;Sung et al, 2012;Zhang et al, 2014). Notably, HDAC2 and HDAC6 are overexpressed in the cortex and hippocampus of AD patients, although the cause and effect of this upregulation remains unknown (Ding et al, 2008;Graff et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, this can also be due to other HDAC6 functions, such as its ubiquitin-binding ability [38,180,181]. Importantly, inhibition of HDAC6 with selective Tubulin acetylation: responsible enzymes, biological functions and human diseases inhibitors promotes tubulin acetylation and significantly improves learning-based performance in mice with bamyloid-induced hippocampal lesions [182,183].…”
Section: Tubulin Acetylation Human Diseases and Therapeutic Implicatmentioning
confidence: 99%